2010
DOI: 10.1007/s12253-010-9329-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Disorders After Solid Organ Transplantation—Classification, Incidence, Risk Factors, Early Detection and Treatment Options

Abstract: Posttransplant lymphoproliferative disorder (PTLD) is a heterogeneous disease group of benign and malignant entities. The new World Health Organisation classification introduced in 2008 distinguishes early lesions, polymorphic, monomorphic and classical Hodgkin lymphoma-type PTLD. Based on the time of appearance, early and late forms can be identified.PTLDs are the second most frequent posttransplantation tumors in adulthood, and the most frequent ones in childhood. The incidence varies with the transplanted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 100 publications
0
78
0
4
Order By: Relevance
“…[3][4][5][6][7] Similarly, effective salvage therapies are lacking for subsets of DLBCL, such as the mediastinal variant of DLBCL, and other aggressive NHLs, such as gray zone lymphomas (B-cell lymphoma unclassifiable with features intermediate between DLBCL and classical Hodgkin lymphoma [HL]) and posttransplant lymphoproliferative disorders (PTLDs). [8][9][10][11][12] CD30 is expressed in a variety of malignancies 13,14 and is present in 14% to 25% of DLBCL patients, depending on the cutoff used to assign positivity. [15][16][17] Hu et al reported a unique gene expression profile for de novo DLBCL expressing CD30 in greater than 20% of cells.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Similarly, effective salvage therapies are lacking for subsets of DLBCL, such as the mediastinal variant of DLBCL, and other aggressive NHLs, such as gray zone lymphomas (B-cell lymphoma unclassifiable with features intermediate between DLBCL and classical Hodgkin lymphoma [HL]) and posttransplant lymphoproliferative disorders (PTLDs). [8][9][10][11][12] CD30 is expressed in a variety of malignancies 13,14 and is present in 14% to 25% of DLBCL patients, depending on the cutoff used to assign positivity. [15][16][17] Hu et al reported a unique gene expression profile for de novo DLBCL expressing CD30 in greater than 20% of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Primary intrarenal localization is extremely rare and is generally diagnosed late, because of ambiguous clinical presentation (2). We detected primary intrarenal lymphoplasmacellular early PTLD in a 5-year-old kidney transplant recipient by renal allograft protocol biopsy.…”
Section: Primary Intrarenal Posttransplant Lymphoproliferative Disordmentioning
confidence: 89%
“…Puede ocurrir en cualquier momento después del trasplante. El tercer grupo corresponde a la ELPT monomorfa de células B o T (22)(23)(24). En la tabla 2 se muestra la clasificación con los diferentes subtipos así como la asociación descrita en cada uno de ellos con el VEB.…”
Section: Clasificación Y Presentación Clínicaunclassified
“…Los estudios de imágenes del sistema nervioso central y el del líquido cefalorraquídeo se hacen según la indicación clínica (5,28). La tomografía computarizada por emisión de positrones (PET-CT) puede ser una alternativa útil, especialmente en los casos de presentaciones atípicas, tanto para evaluar el estadio como para el seguimiento, especialmente en los linfomas B difusos de células grandes y en los linfomas Hodgkin (23,29). Se debe clasificar a los pacientes usando el sistema Ann Arbor, se acuerdo con la localización del compromiso y la presencia de síntomas (30).…”
Section: Estudio Sugerido Para Los Pacientes Con Sospecha De Elptunclassified